Criação de plataforma digital para teleatendimento médico voluntário em meio a pandemia pelo COVID-19 - Ramos, Heloisa Moreira Estrela Diniz (2021)
COVID-19 is a disease caused by the SARS-CoV-2 coronavirus, which presents a clinical condition that varies from asymptomatic infections to severe respiratory conditions. According to the World Health Organization (WHO), most patients with COVID-19 (approximately 80%) may be asymptomatic and approximately 20% of cases may require hospital care due to breathing difficulty and of these cases approximately 5% may need support for the treatment of respiratory failure with ventilatory support. In a world scenario in the face of a pandemic as never seen before in humanity, linked to a need for social isolation imposed by the federal, state and municipal governments, as well as the technological advance in which most people have a device for communication through the internet, the Corona Central Platform was designed and implemented. The aim of the study was to characterize the process of elaboration of the Corona Central Platform: a medical tele-service platform aimed at providing health care to patients with suspected signs and symptoms of COVID-19. The present study can be characterized as na applied, qualitative, cross-sectional analysis of a study of the type of intervention. It is a technological product that fits into the category of intervention product that plays an important role in containing the coronavirus pandemic. The benefits for society are expansion of Primary Care, provision of health services in remote areas, prevention, diagnosis and treatment of diseases and others. To validate the platform, further studies are needed with population samples that can legitimize the system, using reference scales and increasing knowledge on the subject in the scientific area.